Flexibility Management in Renewable Energy Source Operated Power Systems using Decision Support System - Wang, Haoxiang (Journal of Electrical Engineering and Automation, 2020)
In the recent days, energy mix performed by using the Renewable Energy Sources (RES) is gaining wide popularity. The control of predictability and generation takes a progressive loss as RES is penetrating increasingly in the energy mixes due to the non dispatchable nature of the energy produced from these sources. For ensuring and maintaining stable operation, the power system flexibility is increased when higher penetration levels are attained by RES. A Decision Support System (DSS) is used for energy conversion and storage systems which can be managed by an Information and Communication Technology (ICT) tool. The H2020 PLAnning and operational tools are used for optimizing energy flows and synergies between energy NETworks (PLANET) along with DSS for controlling the technology wherein power is converted into either heat or gas (P2X) by evaluation, management and dispatch. Further analysis is done in terms of energy evaluation and economic benefits with respect to P2X technology and its flexibility
Keywords: Decision Support System; Energy Conversion; Flexibility; Sustainability; Renewable Energy Integration